Cytotoxicity Analysis and In Silico Studies of Three Plant Extracts with Potential Application in Treatment of Endothelial Dysfunction - Andreea Roxana Ungureanu; Violeta Popovici; Camelia Oprean; Corina Danciu; Verginica Schröder; Octavian Tudorel Olaru; Dragoș Paul Mihai; Liliana Popescu; Emanuela-Alice Luță; Carmen Lidia Chițescu; Cerasela Elena Gîrd (MDPI AG, 2023)
Endothelial dysfunction is the basis of the physiopathological mechanisms of vascular diseases. In addition to the therapeutic activity of plant extracts, cytotoxicity is significant. This research evaluates the cytotoxicity of three vegetal extracts (Calendulae flos extract-CE, Ginkgo bilobae folium extract-GE, and Sophorae flos extract-SE). In vitro evaluation was performed using an endothelial cell line model (Human Pulmonary Artery Endothelial Cells-HPAEC) when a dose-dependent cytotoxic activity was observed after 72 h. The IC50 values were calculated for all extracts: Calendulae flos extract (IC50 = 91.36 μg/mL), Sophorae flos extract (IC50 = 68.61 μg/mL), and Ginkgo bilobae folium extract (IC50 = 13.08 μg/mL). Therefore, at the level of HPAEC cells, the cytotoxicity of the extracts follows the order GE > SE > CE. The apoptotic mechanism implied in cell death was predicted for several phytocompounds using the PASS algorithm and molecular docking simulations, highlighting potential interactions with caspases-3 and -8. In vivo analysis was performed through brine shrimp lethality assay (BSLA) when lethal, behavioral, and cytological effects were evaluated on Artemia salina larvae. The viability examined after 24 h (assessment of lethal effects) follows the same sequence: CE > SE > GE. In addition, the predicted cell permeability was observed mainly for GE constituents through in silico studies. However, the extracts can be considered nontoxic according to Clarckson's criteria because no BSL% was registered at 1200 µg/mL. The obtained data reveal that all three extracts are safe for human use and suitable for incorporation in further pharmaceutical formulations.